The effect of bio-fertilizers on yield component, yield, protein and oil in soybean (Glycine max Merrill) under different irrigation regimes - majid ghanbari; Ali Mokhtassi-Bidgoli; Parniyan Talebi-Siah Saran (فیزیولوژی محیطی گیاهی, 2019)
The purpose of this study, Evaluation effect of Azotobacter nitrogen fixation bacteria in combination with Pseudomonas putida phosphate solubilizing bacteria on reducing the effects of irrigation water shortage on soybean cultivars under field conditions has been studied. This research was carried out as a factorial experiment in a randomized complete block design with three replications in Tarbiat Modarres University during 2015-2016. Irrigation treatments included optimal irrigation, mild stress, moderate stress and severe stress based on 15, 30, 45 and 60 percent of available water depletion respectively from the establishment time to the end of the growth period and four levels of soybean inoculation with bacteria (control or without bacteria, inoculum with Azotobacter, inoculation with Pseudomonas putida, and inoculation with both bacteria) are considered. The results of this study showed that the main effect of irrigation regime on all traits except 1000 seed weight and the main effect of bio-fertilizer were significant except for 1000 seed weight, seed nitrogen and oil on all traits. From the test results, one can conclude that Azotobacter alone increased 17.9% seed yield, Pseudomonas putida alone increased the yield of 32.4% and the combined application of both bacteria increased the grain yield by 39.8%. In general, considering the non-insignificant effect of bio-fertilizer interaction on levels of water stress, it can be concluded that under favorable irrigation conditions and under drought conditions, the application of bio-fertilizer is effective in improving yield and yield components, protein and oil yield of soybean.